“Endochitinase and Chitobiosidase Production by Marine Aeromonas caviae CHZ306: Establishment of Nitrogen Supplementation“ - Cardozo, Flavio (2023)
“Aeromonas caviae CHZ306, a marine-derived bacterium isolated from zooplankton, can use chitin (a polymer of a β-(1,4)-linked N-acetyl-D-glucosamine) as a carbon source. The chitin is hydrolyzed by chitinolytic enzymes, namely endochitinases and exochitinases (chitobiosidase and N-acetyl-glucosaminidase). Indeed, the chitinolytic pathway is initiated by the coexpression of the enzymes endochitinase (EnCh) and chitobiosidase (ChB); however, few studies, including biotechnological production of these enzymes, have been reported, although chitosaccharide are helpful in several industries, such as cosmetics. This study demonstrates the potential to maximize the simultaneous EnCh and ChB production by nitrogen supplementation on culture media. Twelve different nitrogen supplementation sources (inorganic and organic) previously analyzed in elemental composition (carbon and nitrogen) were tested and evaluated in the Erlenmeyer flask culture of A. caviae CHZ306 for EnCh and ChB expression. None of the nutrients inhibited bacterial growth, and the maximum activity in both EnCh and ChB was observed at 12 h, using corn-steep solids and peptone A. Corn-steep solids and peptone A were then combined at three ratios (1:1, 1:2, and 2:1) to maximize the production. The high activities for EnCh (30.1 U.L−1 ) and ChB (21.3 U.L−1 ) were obtained with 2:1 corn-steep solids and peptone A, corresponding to more than 5- and 3-fold enhancement, respectively, compared to the control condition.“